2011
DOI: 10.1029/2011gl049549
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of hypoxic and acidic events by La Niña conditions on the continental shelf off California

Abstract: [1] Low-oxygen and low-pH events are an increasing concern and threat in the Eastern Pacific coastal waters, and can be lethal for benthic and demersal organisms on the continental shelf. The normal seasonal cycle includes uplifting of isopycnals during upwelling in spring, which brings low-oxygen and low-pH water onto the shelf. Five years of continuous observations of subsurface dissolved oxygen off Southern California, reveal large additional oxygen deficiencies relative to the seasonal cycle during the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 24 publications
8
65
1
1
Order By: Relevance
“…Coastal upwelling ecosystems, such as the California Current System (CalCS), support some of the world's most productive fisheries due to the seasonal, wind-driven upwelling of nutrient-rich waters (e.g., Chavez and Messié, 2009;Messié et al, 2009). The upwelled waters fuel biological production in the CalCS but are also characterized by lower O 2 and lower pH than the surrounding surface waters (e.g., Bograd et al, 2008;Nam et al, 2011). Although the CalCS is accustomed to seasonal fluctuations in O 2 and pH, several observational studies sug-gest that both have decreased in the last decades, particularly within 100 km of the coast (e.g., Bograd et al, 2008;Feely et al, 2008;Nam et al, 2011;Bednaršek et al, 2014;Bednaršek and Ohman, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coastal upwelling ecosystems, such as the California Current System (CalCS), support some of the world's most productive fisheries due to the seasonal, wind-driven upwelling of nutrient-rich waters (e.g., Chavez and Messié, 2009;Messié et al, 2009). The upwelled waters fuel biological production in the CalCS but are also characterized by lower O 2 and lower pH than the surrounding surface waters (e.g., Bograd et al, 2008;Nam et al, 2011). Although the CalCS is accustomed to seasonal fluctuations in O 2 and pH, several observational studies sug-gest that both have decreased in the last decades, particularly within 100 km of the coast (e.g., Bograd et al, 2008;Feely et al, 2008;Nam et al, 2011;Bednaršek et al, 2014;Bednaršek and Ohman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The upwelled waters fuel biological production in the CalCS but are also characterized by lower O 2 and lower pH than the surrounding surface waters (e.g., Bograd et al, 2008;Nam et al, 2011). Although the CalCS is accustomed to seasonal fluctuations in O 2 and pH, several observational studies sug-gest that both have decreased in the last decades, particularly within 100 km of the coast (e.g., Bograd et al, 2008;Feely et al, 2008;Nam et al, 2011;Bednaršek et al, 2014;Bednaršek and Ohman, 2015). Specifically, Bograd et al (2008) found a shoaling of the hypoxic threshold, which is typically considered to be ∼ 60 µmol kg −1 (Gray et al, 2002;Diaz and Rosenberg, 2008;Vaquer-Sunyer and Duarte, 2008), of up to 90 m in the southern CalCS between 1984and 2006.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some turbulence was caused by the recirculation of the seawater for equilibration. Target pH and oxygen levels were chosen based on values recorded at a location near Scripps (Nam et al, 2011). For this experiment, low pH and high oxygen levels were paired in one treatment, and high pH and low oxygen levels in the other, to attempt to understand organismal responses to the individual parameters.…”
Section: E E Bockmon Et Al: Controlled Experimental Aquarium Systementioning
confidence: 99%